2018
DOI: 10.3390/met8100781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Y, GdCu, and Al Addition on the Thermoelectric Behavior of CoCrFeNi High Entropy Alloys

Abstract: Thermoelectric (TE) materials can interconvert waste heat into electricity, which will become alternative energy sources in the future. The high-entropy alloys (HEAs) as a new class of materials are well-known for some excellent properties, such as high friction toughness, excellent fatigue resistance, and corrosion resistance. Here, we present a series of HEAs to be potential candidates for the thermoelectric materials. The thermoelectric properties of Y x CoCrFeNi, Gd x CoCrFeNiCu, and annealed Al 0.3 CoCrFe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…It is interesting to compare the structure reported here with that of the same HEA prepared by different methods. It has often been reported 6,15,20,26,49,50 that material casted from the melt may have inhomogeneities in composition and/or be a mixture of two fcc structures, both with a high concentration of the elements. For example Wang et al 51 reported two fcc structures for CrFeCoNiCu alloys made by a casting facility attached to an arc melter.…”
Section: Comparison With Structure Observed By Othersmentioning
confidence: 99%
“…It is interesting to compare the structure reported here with that of the same HEA prepared by different methods. It has often been reported 6,15,20,26,49,50 that material casted from the melt may have inhomogeneities in composition and/or be a mixture of two fcc structures, both with a high concentration of the elements. For example Wang et al 51 reported two fcc structures for CrFeCoNiCu alloys made by a casting facility attached to an arc melter.…”
Section: Comparison With Structure Observed By Othersmentioning
confidence: 99%
“…The transport properties have an interdependency relationship with different forms of materials as shown in Figure 2 [63,64]. Generally, an insulator material may have high Seebeck coefficient and very low electrical and thermal conductivities.…”
Section: Mathematical Formulations and Boundary Conditionsmentioning
confidence: 99%
“…Electrons scattering in highentropy systems can be exacerbated because of high lattice distortion, which has been used to reduce electronic thermal conductivity in thermoelectric materials. As specific tests on electrical properties of HEAs are seldom conducted [91,100,101,102], electrical conductivity is often a property measured to characterize the thermoelectrical performance of materials [86,87,89,103]. The synthesis routes and compositions of NC HEAs can significantly affect their electrical properties.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…As the optimization of thermoelectric performance of HEAs requires a systematic approach rather than programmable high-throughput evaluation, similar nanostructures have been shown to exhibit completely opposing phenomena. For example, adding Gd to the CoCrFeNi system facilitates the formation of nanoscale Laves phases, leading to a decrease in all of its thermoelectric parameters (electrical conductivity, thermal conductivity, and Seebeck coefficient) and having a reduced figure of merit, ZT [89]. In the NC-Ti 2 NiCoSnSb system (grain size ;12 nm), a secondary phase of TiC is obtained after long ball-milling times, facilitating more Ni 3 Sn 4 formation and leading to higher electrical and thermal conductivities, but undermining the thermoelectric performance [103].…”
Section: Thermal Conductivity and Thermoelectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation